Factors Affecting the Response Time of Radiology Result Reading - Gozali, Juliana; Haicha Pritama, Irza; Chiuman, Linda (CV. Inara, 2024)
Respond time is a common issue in healthcare practice. This problem also occurs in radiology services concerning the reading of radiology results to the expert interpretation process by radiologists. This study analyzes departmental and personal factors influencing the response time of radiology result readings at Murni Teguh General Hospital in Medan in 2021. This quantitative research study has a cross-sectional design and an analytical observational approach. The population includes all radiologists in the Radiology Department. Data is collected through questionnaires and documentation. Logistic regression is used for data analysis. The majority of radiology result readings have a poor response time (56.9%). Multivariate analysis reveals that departmental factors (image results and network) and personal factors (work schedule) significantly influence the response time of radiology result readings. However, there is no significant influence from departmental factors (teaching obligations) and personal factors (educational level and employment status) on the response time of radiology result readings. It is recommended that hospital management cultivate a collaborative and supportive environment among the technology and human resources working in the Radiology Department to improve the response time by the standards set by the ministry.